2015
DOI: 10.3892/mmr.2015.3978
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between thyroglobulin gene polymorphisms and autoimmune thyroid disease

Abstract: Abstract. The aim of the present study was to detect thyroglobulin (Tg) gene polymorphisms in a Han Chinese population from the Northern regions of Henan province, China, and to study the correlation between Tg gene polymorphisms and autoimmune thyroid disease (AITD). A total of 270 patients with AITD and 135 healthy controls were enrolled. Genomic DNA was extracted and fluorescence polymerase chain reaction analysis was performed; high-resolution melting curve analysis (HRMA) was used to detect single-nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…TG is a 660-kDa glycoprotein, which accounts for about 75%-80% of the total thyroid protein [25,26] and deserves to be a major AITDs susceptibility gene. Earlier researches have recognized that TG SNPs were related to the development of AITDs [27][28][29][30][31]. In 2011, Mihaela Stefan et al revealed a new mechanism of interaction between the TG promoter SNP variant with viral infection to AITDs, which laid the foundation for further exploration [32].…”
Section: Discussionmentioning
confidence: 99%
“…TG is a 660-kDa glycoprotein, which accounts for about 75%-80% of the total thyroid protein [25,26] and deserves to be a major AITDs susceptibility gene. Earlier researches have recognized that TG SNPs were related to the development of AITDs [27][28][29][30][31]. In 2011, Mihaela Stefan et al revealed a new mechanism of interaction between the TG promoter SNP variant with viral infection to AITDs, which laid the foundation for further exploration [32].…”
Section: Discussionmentioning
confidence: 99%
“…This condition is probably because the organ is genetically sensitive to autoimmunity in some individuals. Multiple studies performed in various populations found out certain single-nucleotide polymorphisms (SNPs) to be associated with thyroid autoimmunity or their comorbidities with other diseases [17,18]. All these observations suggested that the detection of anti-thyroid antibodies may be part of the autoimmunological profile triggered by patients with autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The haploid allele combination analysis of TG polymorphic loci, E10SNP24-E10SNP158-E12SNP-E33SNP, was performed between the hyperthyroidism group and the healthy group. The disease-linked haplotypes G-T-A-C, G-T-G-C and T-C-G-C was significantly different (P<0.05) (13). In case control studies, several SNPs in exons 10, 12, and 33 were significantly associated with AITD (14) or with GD relapse (15).…”
Section: Introductionmentioning
confidence: 90%